The EFEKTIVITAS LATIHAN TERA TERHADAP TINGKAT GULA DARAH PADA PENDERITA DIABETES MELLITUS Tipe 2 : Kadar gula darah - Riska Rohmawati; Imamatul Faizah; Ratna Yunita Sari (Nurse and Health: Jurnal Keperawatan, 2026)
Background: Blood sugar levels in type 2 DM sufferers tend to increase mildly but progressively because they are low self-care management in people with type 2 DM. One non-pharmacological therapy that can help blood sugar levels remain stable is tera exercise. Purpose: This study aimed to analyze the effectiveness of tera exercise on blood sugar levels in type 2 DM sufferers at the Wonokromo Community Health Center. Methods: The design of this study is RCT (Randomized Controlled Trial). The number of samples for each group was 24 in the control group and 24 in the intervention group. The study was conducted at the Wonokromo Community Health Center from July – 4 August times, every Tuesday and Friday for 2 weeks, with a duration of 45 minutes, using the technique of Simple Random Sampling. The independent variable in this study is physical exercise, and the dependent variable is blood sugar levels. The instrument in this study was the tera gymnastics SOP and blood sugar level observation sheet. The statistical test used is paired t-test and independent t-test with a significance level of α = 0.05. Results: The test result obtained a p-value of 0.000, which means that there is a significant difference in blood sugar levels before and after participating in tera exercise activities. Test results independent t-test A significant value was obtained of 0.034 (p < 0.05), which means tera exercise influences the blood sugar levels of type 2 DM patients at the Wonokromo Community Health Center Conclusion: Tera exercise effectively reduces blood sugar levels in type 2 DM sufferers at the Wonokromo Community Health Center. The term exercise is hoped to be used as an independent intervention in the elderly posyandu program at the Wonokromo Community Health Center